2008
DOI: 10.1016/j.pscychresns.2007.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Neural systems for executive and emotional processing are modulated by symptoms of posttraumatic stress disorder in Iraq War veterans

Abstract: The symptom provocation paradigms generally used in neuroimaging studies of posttraumatic stress disorder (PTSD) have placed high demands on emotion processing but lacked cognitive processing, thereby limiting the ability to assess alterations in neural systems that subserve executive functions and their interactions with emotion processing. Thirty-nine veterans from Iraq and Afghanistan underwent functional MR imaging while exposed to emotional combat-related and neutral civilian scenes interleaved with an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
89
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 77 publications
(116 reference statements)
14
89
1
Order By: Relevance
“…Preliminary findings from Roy and colleagues (2010) showed that successful PTSD treatment (e.g., through the use of exposure therapy delivered via virtual reality or prolonged imaginal exposure) was associated with decreased activation in the amygdala, subcallosal gyrus, and lateral prefrontal cortex. Importantly, these regions are similar to those identified as hyperactive in previous studies of OEF/OIF Veterans (e.g., Morey, et al, 2008), suggesting that successful treatment for PTSD might be associated with a dampening of hyper-sensitivity of these regions. Combined with studies examining the correlation between PTSD symptoms and neurofunctional responses, a distributed network emerges in which structures subserving emotion appear to be negatively correlated to symptoms of combat-related PTSD, while those subserving both cognition and emotion seem to be positively correlated (Figure 3).…”
Section: Functional Neuroimaging Studiessupporting
confidence: 80%
“…Preliminary findings from Roy and colleagues (2010) showed that successful PTSD treatment (e.g., through the use of exposure therapy delivered via virtual reality or prolonged imaginal exposure) was associated with decreased activation in the amygdala, subcallosal gyrus, and lateral prefrontal cortex. Importantly, these regions are similar to those identified as hyperactive in previous studies of OEF/OIF Veterans (e.g., Morey, et al, 2008), suggesting that successful treatment for PTSD might be associated with a dampening of hyper-sensitivity of these regions. Combined with studies examining the correlation between PTSD symptoms and neurofunctional responses, a distributed network emerges in which structures subserving emotion appear to be negatively correlated to symptoms of combat-related PTSD, while those subserving both cognition and emotion seem to be positively correlated (Figure 3).…”
Section: Functional Neuroimaging Studiessupporting
confidence: 80%
“…Instructions at the beginning of the task directed participants to keep their gaze in the center of the screen at all times. The delay-spanning images were drawn from a previous study conducted in military populations (Morey et al 2008). The negative stimuli were generated from internet searches and photo collections of soldiers that depicted combat-related scenes from Afghanistan and Iraq, while the neutral stimuli depicted civilian scenes that matched the negative stimuli in terms of figure/scene ratio, scene complexity, and chromatic structure.…”
Section: Experimental Stimuli and Designmentioning
confidence: 99%
“…These findings suggest that salient negative stimuli, despite being task-irrelevant, capture attention and interfere with ongoing maintenance of task-relevant memoranda leading to decreased WM performance. These stimuli may be similar to what is encountered in the external environment under highstress circumstances (Morey et al 2008(Morey et al , 2009). Several studies have now reported that WM task performance is worse for trials on which negative vs. neutral distracters are presented (Beblo et al 2010;Morey et al 2008Morey et al , 2009Oei et al 2012), with even greater performance costs under experimentally-induced stress (Oei et al 2006).…”
mentioning
confidence: 99%
“…Here the results are mixed. Activation in dorsal ACC was decreased during the detection of neutral targets (Morey et al 2008), normal in the conflict condition of the counting Stroop task (Shin et al, 2007), and increased in the multisource interference task (Shin et al 2011). On the basis of these conflicting fMRI results, it would be difficult to make a prediction about any larger implications for the error monitoring system.…”
Section: Anterior Cingulate Cortex and Ptsdmentioning
confidence: 99%